Effects of Direct and Indirect Factors on Attitude toward the COVID-19 Vaccine in Pregnant Women - Dora Samaria; Desmawati Desmawati; Lima Florensia (Nurse Media Journal of Nursing, 2023)
Background: The administration of the COVID-19 vaccine is facing resistance from pregnant women, leading to a lower attitude toward vaccination uptake. Previous studies have explored several factors that contributed to the issue. However, no studies have investigated further the direct and indirect effects of factors that simultaneously influence attitudes toward the COVID-19 vaccine in pregnant women. Purpose: This study aimed to investigate the direct and indirect effects of factors that influence attitudes toward the COVID-19 vaccine (ACV) in pregnant women, particularly hesitancy, motivation, and history of COVID-19 infection (HCI), and to describe a pathway model that represents the effects.Methods: This cross-sectional study recruited 440 pregnant women living in Bekasi and Pandeglang, Indonesia, in May–June 2022 using consecutive sampling methods. This study employed the Motivations of Vaccination Questionnaire, the Reasons for Hesitation Questionnaire, and the Attitudes toward COVID-19 Vaccine Questionnaire. A path analysis was performed to calculate the data.Results: Hesitancy had a more indirect effect (β=-0.270; p=0.00) than the direct effect (β=-0.193; p=0.00) on ACV, whereas motivation had a more direct effect (β=0.092; p=0.04) than the indirect effect (β=0.074; p=0.00). HCI acted as the mediation variable because it could intercede with the effect of hesitancy on ACV (β=-0.449; p=0.00). It indicated that HCI in pregnant women would lead to a different approach to increasing ACV.Conclusions: All studied factors had significant impacts on ACV, both directly and indirectly. It is recommended that interventions be adjusted according to the program’s purpose, with the aim of increasing motivation or reducing hesitancy.